Analisis Perbandingan Tipe Pelumas Berdasarkan Wujud pada Studi Kasus Pelumasan pada Gearbox Sepeda Motor - Muhammad, Fadhil Burhanuddin (Jurnal Rekayasa Mesin, 2015)
Lubricants have a very wide application in all aspects of life, including industry and automotive sectors. The main purpose of a lubricant is to keep the moving/sliding surfaces apart, so that friction and consequent destruction of material is minimized. Lubricants can be solid, semi-solid, liquid, or gas. The research method in this study composed of data collecting through library method, the theory structures consist of explanation of the advantages and disadvantages of each type of lubricant as well as the working conditions on the given case study. The working conditions of the case study are used as the parameters to the feasibility of lubricants on case study, the parameters are the ability to receive the load, the ability to survive at a speed of 700-3000 rpm, the ability to be circulated, the ability to do the filtering, and the ability to do the cooling. Based on the results obtained from literature study, found that the good ability to receive a load owned by lubricants semi-solid and liquid, the ability to survive at a speed of 700-3000 rpm only owned by liquid lubricant, the ability to be circulated owned by liquid lubricants and gas, the ability to do filtering owned liquid lubricant and gas, and the ability to perform cooling owned by liquid lubricant and gas. Based on the results of the final analysis, the best lubricant that suitable for the case study is liquid lubricant.